THE ROLE OF ACCOUNT EXECUTIVE AND SOCIAL MEDIA SPECIALIST IN DEVELOPING AN INTEGRATED MARKETING COMMUNICATION STRATEGY TO INCREASE PRODUCT USAGE CONVERSION OF BY.U BY TELKOMSEL - Viola Prameswari; Nurist Surraya Ulfa (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2026)
By.U, a digital cellular service launched by Telkomsel is a provider that specifically targets Generation Zand young Digital users. Despite its positioning as a young-oriented digital provider, along with its effortswhich align with the young generation needs, the level of by.U usage among high school students inSemarang remains relatively low. A preliminary survey conducted among 814 students from four selectedschools affiliated with Telkomsel educational platform, Skul.Id, revealed that only 5.7% (46 students)were active users of the by.U SIM card. the survey also indicated a high level of perceived risk towardsby.U service at 54.5%, along with a low purchase intention of only 20,8%. In response to thesechallenges, an Integrated Marketing Communication (IMC) strategy was designed and implementedthrough the campaigns, namely “by.U On The Move!” And the “by.U Inter-School Digital Challenge”.These campaigns aimed to increase brand trust, reducing perceived risk, and increasing the purchasedesire among students by providing direct experiential interactions with the product through both offlineand online activation. The implementation of the campaign resulted in significant improvements acrossvarious key indicators. The number of by.U users among students increased from 46 users (5.7%) to 118users (14.5%). Along with that, the level of perceived risk toward by.U service decreased substantiallyfrm 54.5% to 19,5%. Additionally, the students purchase intention toward by.U showed a considerableincrease, inclined from 20,8% to 72.8% following the implementation and exposure of the by.U On TheMove and by.U Interschool Digital Challenge Campaign. As an Account Executive and Social Media Specialist, the author was responsible for managing clientcommunication, coordinating stakeholders, as well as executing digital communication strategies,including media partners and influencer collaboration. This report documents the effectiveness of theimplemented communication strategies and provides insights for future integrated marketingcommunication campaigns targeting youth audiences.